Development of Surface Coating based Hybrid Acrylic Copolymers for Coating Application, Preparation, Characterization and Processing - Farah Safi Khliwi; Mohamed Ali Mutar; Ramaah Abdulhassan Sabit; Entidhar Kadhim Sahib (Institute of Medico-legal Publications Pvt Ltd, 2021)
In this study, series of hybrid emulsion copolymers with different composition ratios of acrylic acid, methylacrylicacid with butyle-acrylate, methyl-metha-acrylate, polyvinyl alcohol were generated. The preparationwas performed in a batch reactor on an industrial scale to obtain the resulting resin. While applying variousprocesses of emulsion polymerization, batch polymerization was chosen to find optimum conditions byinvestigating the parameters of the monomer percentages, initiators, temperature and time. Dodecyl BenzeneSulphonic acid SDBA as emulsifier, as well as sodium dodecyl sulfonic acid SDBAS as co-emulsifier asredox couple initiator have been chosen as the best and most effective initiators to hybrid acrylic resinprocessing Water-dispersed acrylic resin was developed as a hydrophilic monomer, utilizing acrylic acid.To avoid gelatin and agglomeration, the reaction temperature of the acrylic resin preparation was takenfor 4 hours at 70oC. To understand the effect of silane coupling agent on the properties of hybrid emulsioncopolymers, in the presence of trimetyl-chloro saline. FTIR spectroscopy, 1HNMR spectra, thermal analysisas well as mechanical tests were widely studied confirmation of the hybrid acrylic resins. The various physicchemicalproperties of hybrid emulsion acrylic copolymers including density, viscosity, chemical resistanceand volatile matter were studied. The results show that hybrid emulsion acrylic copolymers are readilysoluble in aprotic polar solvents such as (Toluene, Acetone, Benzene, xylene, DMF, DMSO, Methanol, andethanol) without being in need for heating. The emulsion copolymers obtained had a great solid content aswell as have been used as binder in emulsion paints. These polymers have very useful properties such ashigh anticorrosive and chemical resistance, the experimental results reveal.